Some Properties On μ-Metrics Induced By An Intuitionistic Fuzzy Metric Spaces - et. al., S. Yahya Mohamad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The idea of Intuitionistic Fuzzy Metric Space introduced by Park (2004). In this paper, a new concept of upper -metrics and lower -metrics by which the distance between two points are calculated upto the degree of correctness parameter of crisp metrics induced by a Intuitionistic Fuzzy Metric Space is introduced also discuss some properties of -metrics on Intuitionistic fuzzy metric spaces.